Visualization-Based Discovery of Vanin-1 Inhibitors for Colitis - Wang, Guankai; Wang, Jingjing; Du, Lupei; Li, Minyong (Frontiers in Chemistry, 2022)
The main effect of Vanin-1 (VNN1) is related to its pantetheinase sulfhydrylase activity, which may hydrolyze pantetheine to produce pantothenic acid and cysteamine. The enzymatic activity of VNN1 has been discovered to be critical in the development of various disorders. Specific VNN1 inhibitors are being studied to have a better understanding of their involvement in the illness process. Using pyrimidine amide as lead compounds, various inhibitors were developed and synthesized in this study. To screen inhibitors intuitively, this study designed and synthesized a fluorescent probe PA-AFC for in vitro evaluation of inhibitors with high sensitivity and specificity. The bioluminescent probe PA-AL was then utilized to assess inhibitors at the cellular level and in vivo with simple, cost-effective, and extremely accurate characters. Finally, these inhibitors were tested in a mouse colitis model, confirming their utility in inflammatory bowel disease (IBD) and pointing to a novel treatment avenue.